2003
DOI: 10.1017/s0952836903004254
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin secretion in a strictly subterranean mammal, the Damaraland mole‐rat (Cryptomys damarensis)

Abstract: Subterranean mammals inhabit an environment that is normally devoid of light and are therefore deprived of photoperiodic information that can be used to time important life-history events. An assessment was made of whether melatonin secretion in a strictly subterranean rodent, the Damaraland mole-rat Cryptomys damarensis, can be modified by photoperiod. In experiment 1, a clear diurnal rhythm of melatonin secretion in animals housed under a neutral photoperiod (12L:12D) was observed, with significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…The blood plasma melatonin rhythm, which is of pineal origin, shows mean daytime levels of PMC that are lower than those values measured at night. This is consistent with many other mammals, such as the Syrian (Mesocricetus auratus) and the Djungarian (Phodopus sungorus) hamster [18,19], the valley pocket gopher (Thomomys bottae) [2] and the Damaraland mole-rat (C. damarensis) [12] to compare some rodents living in a similar habitat. In experiment 1, levels of PMC exhibited an endogenous rhythm that conforms to the findings of locomotory activity patterns of this species measured via e-mitter, IR captors and running wheel [14].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The blood plasma melatonin rhythm, which is of pineal origin, shows mean daytime levels of PMC that are lower than those values measured at night. This is consistent with many other mammals, such as the Syrian (Mesocricetus auratus) and the Djungarian (Phodopus sungorus) hamster [18,19], the valley pocket gopher (Thomomys bottae) [2] and the Damaraland mole-rat (C. damarensis) [12] to compare some rodents living in a similar habitat. In experiment 1, levels of PMC exhibited an endogenous rhythm that conforms to the findings of locomotory activity patterns of this species measured via e-mitter, IR captors and running wheel [14].…”
Section: Discussionsupporting
confidence: 85%
“…The presence of light resulted in low levels of PMCs at T12 on day 2 in LL animals, with no difference between the two sample times, while showing a small standard error. This result contrasts findings with a sister taxon the Damaraland mole-rat [12] as well as the valley pocket gopher [2] but is consistent, for example, with the laboratory rat [23]. According to Reiter et al [2] and Richter et al [12] the valley pocket gopher and Damaraland mole-rat are diurnal species.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…All species thus far investigated display locomotor activity rhythms that can be entrained to light (Hart et al, 2004;Oosthuizen et al, 2003;Riccio & Goldman, 2000a;Schöttner et al, 2006;Vasicek et al, 2005a). In addition, melatonin secretion (Gutjahr et al, 2004, Hart et al, 2004Richter et al, 2003;Vasicek et al, 2005b) and body temperature (Lovegrove & Muir, 1996;Riccio & Goldman, 2000b) also show rhythmic cycles and light can suppress melatonin secretion in the blind mole-rat (Zubidat et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…All species investigated thus far display locomotor activity rhythms loosely entrained to light under experimental conditions (e.g. Lovegrove & Papenfus 1995;Riccio & Goldman 2000;Oosthuizen et al 2003;Hart et al 2004;Vasicek et al 2005;Schottner et al 2006), and circadian rhythms of melatonin secretion (Richter et al 2003;Gutjahr et al 2004;Vasicek et al 2005) and body temperature (Lovegrove & Muir 1996;Riccio & Goldman 2000). Nevertheless, field studies have suggested that burrow temperature could also be an important stimulus for entraining circadian activity under natural conditions ( Skl ıba et al 2007( Skl ıba et al , 2014.…”
Section: Introductionmentioning
confidence: 99%